DEVEOPING AN IDEAL LEADERSHIP SUCCESSION MODEL FOR THE MALAYSIAN PUBLIC SERVICE - Mohd Hafizzuddin Md Damiri (Jurnal Manajemen Pelayanan Publik, 2019)
Leadership succession in the Malaysian Public Service’s higher management has been seen as one of the most important task for Jabatan Perkhidmatan Awam (JPA). This department acts as the centralized administrator for human resources for the whole of the Malaysian Public Service – excluding the Royal Malaysian Police (PDRM) and the Malaysian Armed Forces (ATM) – and determines the career path for all schemes under their purview, which includes officials of the Perkhidmatan Tadbir dan Diplomatik (PTD), the Pegawai Perkhidmatan Latihan dan Vokasional (PPLV) and the Pegawai Perkhidmatan Psikologi (PPPsi). This paper will review the hypothetical leadership succession strategies and any developed models in the Malaysian public sector, through various available literatures, guidelines and processes.